The high Middle Ages - Daileader, Philip; Stonebarger, Tamara; Teaching Company (Chantilly, Va. : Teaching Co., 2001)
This course of twenty-four lectures examines the period know as the High Middle Ages (1000-1300). The first eight lectures cover medieval society. Lectures nine through sixteen examine the intellectual and religious history of Europe during this period. The final eight lectures cover the major political developments and events.
part I: 1. Why the Middle Ages? -- 2. Demography and the commercial revolution -- 3. Those who fought: the nobles -- 4. The chivalric code -- 5. Feudalism -- 6. Those who worked: the peasants -- 7. Those who worked: the townspeople -- 8. Women in medieval society -- 9. Those who prayed: the monks -- 10. Francis of Assisi & the Franciscan movement -- 11. Heretics & heresy -- 12. The medieval inquisitions. -- part II: 13. Jews & Christians -- 14. The origins of scholasticism -- 15. Aquinas & the problem of Aristotle -- 16. The first universities -- 17. The People's Crusade -- 18. The conquest of Jerusalem -- 19. The Norman Conquest -- 20. Philip II of France -- 21. Magna Carta -- 22. Empire versus papacy -- 23. Emperor Frederick II -- 24. Looking back, looking forward.
Each lecture is 35-40 min. In 2 containers (25 x 17 cm.)
24 lectures on 4 discs, 2 discs in each container.
Producer: Tamara Stonebarger.
Lecturer: Philip Daileader, College of William and Mary.
DVD, region 1.
Keywords: Middle Ages; Civilization, Medieval; Europe -- History -- 476-1492.